2016
DOI: 10.3233/wor-152222
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal risks associated with nurses and nursing assistants handling overweight and obese patients: A literature review

Abstract: Abstract.BACKGROUND: Nurses and nursing assistants are susceptible to work-related musculoskeletal disorders and injuries (WMSDs) due to the increase in overweight and obese patients they are handling on a daily basis. OBJECTIVE: This study aimed to review work-related musculoskeletal hazards and risks associated with handling overweight and obese patients, and summarize the recommended interventions to mitigate musculoskeletal concerns among nurses and nursing assistants. METHODS: Approximately 350 publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 26 publications
(65 reference statements)
1
82
0
2
Order By: Relevance
“…[62] Some studies found that musculoskeletal disorders have been consistently associated with patient-handling among nurses. [63,64] The highest rates of non-fatal occupational musculoskeletal disorders have been reported among nurses than in any other healthcare professionals. [65] However, it is recommended that healthcare organizations should provide a healthful working schedule that is required to prevent the risk of musculoskeletal disorders among nurses, they also should provide educational programs which consider Good Body Mechanics by an informal policy.…”
Section: Discussionmentioning
confidence: 99%
“…[62] Some studies found that musculoskeletal disorders have been consistently associated with patient-handling among nurses. [63,64] The highest rates of non-fatal occupational musculoskeletal disorders have been reported among nurses than in any other healthcare professionals. [65] However, it is recommended that healthcare organizations should provide a healthful working schedule that is required to prevent the risk of musculoskeletal disorders among nurses, they also should provide educational programs which consider Good Body Mechanics by an informal policy.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MSDs may vary between 33.0% and 88.0% among nurses all over the world [4,7,12]. The frequency of disorders was found 84.0% and 76.2% in studies performed on nurses in Estonia and Taiwan, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated MSDs is a main occupational health problem in nurses [5,6]. MSDs can have a rigorous consequence on quality of life and may result in work constraints, absenteeism or even the want to change jobs [7]. Nurses are the main hospital workers in frequent close contacts with patients and they are interacting not only with patients but also with instruments and environment in hospital.…”
Section: Introductionmentioning
confidence: 99%
“…We also identified an overall prevalence of MSD as 97%, which was higher than the prevalence of MSD reported by previous studies, conducted at different settings. [11][12][13][14][15][16][17][18][19][20][21] Different body sites were taken into consideration in the analysis and we observed neck, shoulder, upper back and lower back as the most prominent areas which are affected, but among the four only two body sites, the neck and shoulder demonstrated statistical significance. However, according to Yan P et al (2017) the most commonly affected regions were lower back, neck,shoulder, and back, with an annual prevalence of 62.71%, 59.77%, 49.66%, and 39.50%, respectively.…”
Section: Prevalence Of Msdmentioning
confidence: 99%